Mandibular growth and dentoalveolar development in the treatment of Class II, division 1, malocclusion using Balters Bionator according to the skeletal maturation - Santos-pinto, Paulo Roberto Dos (2013)
OBJECTIVE: The purpose of the study was to evaluate the influence of the skeletal maturation in the mandibular and dentoalveolar growth and development during the Class II, division 1, malocclusion correction with Balters bionator. METHODS: Three groups of children with Class II, division 1, malocclusion were evaluated. Two of them were treated for one year with the bionator of Balters appliance in different skeletal ages (Group 1: 6 children, 7 to 8 years old and Group 2: 10 children, 9 to 10 years old) and the other one was followed without treatment (Control Group: 7 children, 8 to 9 years old). Lateral 45 degree cephalometric radiographs were used for the evaluation of the mandibular growth and dentoalveolar development. Tantalum metallic implants were used as fixed and stable references for radiograph superimposition and data acquisition. Student's t test was used in the statistical analysis of the displacement of the points in the condyle, ramus, mandibular base and dental points. Analysis of variance one-fixed criteria was used to evaluate group differences (95% of level of significance). RESULTS: The intragroup evaluation showed that all groups present significant skeletal growth for all points analyzed (1.2 to 3.7 mm), but in an intergroup comparison, the increment of the mandibular growth in the condyle, ramus and mandibular base were not statically different. For the dentoalveolar modifications, the less mature children showed greater labial inclination of the lower incisors (1.86 mm) and the most mature children showed greater first permanent molar extrusion (4.8 mm).